Impact of wheel rotation on the aerodynamic drag of a time trial cyclist - Malizia, F.; van Druenen, T.; Blocken, B. (Sports Engineering, 2021)
Aerodynamic drag is the main resistive force in cycling at high speeds and on flat terrain. In wind tunnel tests or computational fluid dynamics simulations, the aerodynamic drag of cycling wheels is often investigated isolated from the rest of the bicycle, and sometimes in static rather than rotating conditions. It is not yet clear how these testing and simulating conditions influence the wheel aerodynamic performance and how the inclusion of wheel rotation influences the overall measured or computed cyclist drag. This study presents computational fluid dynamics simulations, validated with wind tunnel tests, that indicate that an isolated static spoked front wheel has a 2.2% larger drag area than the same wheel when rotating, and that a non-isolated static spoked front wheel has a 7.1% larger drag area than its rotating counterpart. However, rotating wheels are also subjected to the rotational moment, which increases the total power required to rotate and translate the wheel compared to static conditions where only translation is considered. The interaction with the bicycle frame and forks lowers the drag area of the front wheel by 8.8% for static and by 12.9% for the rotating condition, compared to the drag area of the isolated wheels. A different flow behavior is also found for static versus rotating wheels: large low-pressure regions develop from the hub for rotating wheels, together with a lower streamwise velocity region inside the circumference of the wheel compared to static wheels. The results are intended to help in the selection of testing/simulating methodologies for cycling spoked wheels.